2009
DOI: 10.1021/la902006v
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrasmooth and Highly Stable Copper Surfaces through Annealing and Self-Assembly of Organic Monolayers

Abstract: Copper (Cu) has been extensively used as an interconnect material for microelectronic devices because of its high electrical and thermal conductivity and excellent electromigration resistance. However, the formation of relatively rough Cu surfaces ( approximately 5 nm roughness) and Cu-oxide layers upon exposure to air still hinders their reliable application in a wide range of fields. In this article, we show the potential values of highly stable and ultrasmooth polycrystalline bare Cu obtained by simple anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 94 publications
5
34
0
Order By: Relevance
“…Indeed, the surface roughness of metal oxide surfaces has been shown to have a direct influence on their wetting properties towards water, which in turn could have a direct influence on the formation of the native oxide 296 . In particular, very smooth copper surfaces are hydrophobic while rough surfaces (∼ 5 nm-high roughness) are hydrophilic 297 . Furthermore the orientation of the crystallites at the surface influences the wetting properties and the distribution and coverage of water on the surface, especially in the case of copper 298 .…”
Section: Native Oxidation Of Copper In Ambient Conditionsmentioning
confidence: 99%
“…Indeed, the surface roughness of metal oxide surfaces has been shown to have a direct influence on their wetting properties towards water, which in turn could have a direct influence on the formation of the native oxide 296 . In particular, very smooth copper surfaces are hydrophobic while rough surfaces (∼ 5 nm-high roughness) are hydrophilic 297 . Furthermore the orientation of the crystallites at the surface influences the wetting properties and the distribution and coverage of water on the surface, especially in the case of copper 298 .…”
Section: Native Oxidation Of Copper In Ambient Conditionsmentioning
confidence: 99%
“…66,67 ). Only a few systems have been examined spectroscopically [68][69][70][71][72] whereas molecularly resolved studies using scanning tunneling microscopy (STM) have been performed only rather recently. [62][63][64][65]73 In these studies Au/mica substrates were used onto which a Ag bilayer or a pseudomorphic (√3×√3)R30° Cu layer were electrochemically deposited in the region positive of the Nernst potential (underpotential deposition, UPD) 74 Notably, a very recent STM study demonstrated that also Ag films are suitable substrates for the assembly of ArCA SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…The solution based studies have been performed almost exclusively on fatty acids (for references see reviews by Ulman 29 and Jadhav 30 ) with the exception of terephthalic acid, 31 alkoxy derivatised biphenyl-, naphthyl-and benzenecarboxylic acid, and terphenylcarboxylic acid. [32][33][34] To this small set of spectroscopic studies, benzene-1,3-dicarboxylic acid (isophthalic acid, IPA), benzene-1,3,5-tricarboxylic acid (trimesic acid, TMA) and biphenyl-3,4′,5-tricarboxylic acid (BPTCA) have recently been added.…”
Section: Introductionmentioning
confidence: 99%